The Role of Syrian Christians (Shuwām) in the Nahda Movement of the 19th Century - Turgay Gökgöz (Hitit İlahiyat Dergisi)

(untitled)
After his invasion of Egypt in 1798, Napoleon Bonaparte departed the country in 1802. In 1805, Kavalian Mehmet Ali Pasha, who later became the Khedive of Egypt, took significant measures to modernize Egypt through the Nahda Movement. To keep up with advancements in the West, Kavalian Mehmet Ali Pasha initially focused on translating Western languages, particularly French and Italian - the language of diplomacy at the time - into Arabic and later into Turkish. These Syrians had migrated to Egypt after the first quarter of the 1700s and were present in Egypt after Napoleon’s invasion of Egypt. Finding individuals in Egypt who possessed fluency in both Arabic and foreign languages for these translations was challenging and these characteristics gave Syrian Christians extraordinary advantages that they could not have obtained in Beirut and Syria. In fact, the economic crisis in Bilād al-Shām and the struggles between the Druze and the Maronites and agricultural disasters, famine and many other factors have disturbed the peace of the people and they have started to search for a better place where they can build a better life. In this regard, they saw Egypt as their primary destination. Some immigrants even migrated to the American continent via Cairo and formed a school of what they would call "Mahjar literature" in countries such as the USA, Brazil and Argentina. Cities like Cairo and Alexandria have become centres that have attracted thousands of Christian Syrians and have become an important attraction in the Middle East. Therefore, they were first employed within the framework of the translation movement. In addition, although a school was opened in Egypt to teach French, it was understood that this language was not learnt very well, so Kavalian Mehmet Ali Pasha thought that students should be sent to European countries and learn these languages in their natural environment. As a result, the translations made by immigrant Syrians, the newspapers and journals they founded formed the foundations of the modernisation steps of the Mehmet Ali Pasha period, and science and literature developed, especially among Christian Arabs, and Egypt was able to gain an important position in the Arab world. The contributions of the Syrians extended beyond translations, as they also played a key role in Egypt’s media sector, establishing newspapers and magazines. The translations produced by Syrian immigrants and the newspapers and journals they founded became the building blocks for the modernization efforts during the period of Kavalian Mehmed Ali Pasha. This led to advancements in science and literature, particularly among Christian Arabs, and elevated Egypt to a significant position within the Arab world. In light of this, this article aims to explore the contributions of Syrian Christians who migrated from Bilād al-Shām to Egypt, and their impact on the Nahda Movement through their translations and establishment of newspapers and journals. In this context, this article will try to discuss the contributions of Syrian Christians who migrated to Egypt from the geography of Bilād al-Shām to the Nahda Movement through the translations they made and the newspapers and magazines they established.